2022
DOI: 10.3892/etm.2022.11686
|View full text |Cite
|
Sign up to set email alerts
|

PROSER2 is a poor prognostic biomarker for patients with osteosarcoma and promotes proliferation, migration and invasion of osteosarcoma cells

Abstract: Proline-and serine-rich 2 (PROSER2) is encoded by the 47th open reading frame on human chromosome 10. Bioinformatic analysis has shown PROSER2 was significantly correlated with prognostic outcome of osteosarcoma patients. Its role in the progression and metastasis of human osteosarcoma has not been elucidated until now. Bioinformatics analysis was performed on 101 patients with osteosarcoma from The Cancer Genome Atlas database. High levels of PROSER2 were associated with a poor prognosis in patients with oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Moreover, high PROSER2 expression has been reported to promote cancer cell metastasis in osteosarcoma. 21 However, in this study, a contrasting pattern was observed with no or minimal expression of PROSER2 in advanced-stage pancreatic cancer (GPDOXc), and knockdown of PROSER2 in cells with high expression led to a significant increase in the growth and metastatic capability of cancer cells (Figure 2). This inconsistency may be attributed to differences in the samples analyzed.…”
Section: ■ Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, high PROSER2 expression has been reported to promote cancer cell metastasis in osteosarcoma. 21 However, in this study, a contrasting pattern was observed with no or minimal expression of PROSER2 in advanced-stage pancreatic cancer (GPDOXc), and knockdown of PROSER2 in cells with high expression led to a significant increase in the growth and metastatic capability of cancer cells (Figure 2). This inconsistency may be attributed to differences in the samples analyzed.…”
Section: ■ Discussionmentioning
confidence: 56%
“…Higher expression of PROSER2 is associated with decreased survival rates in pancreatic cancer patients, according to the Human Protein Atlas. Moreover, high PROSER2 expression has been reported to promote cancer cell metastasis in osteosarcoma . However, in this study, a contrasting pattern was observed with no or minimal expression of PROSER2 in advanced-stage pancreatic cancer (GPDOXc), and knockdown of PROSER2 in cells with high expression led to a significant increase in the growth and metastatic capability of cancer cells (Figure ).…”
Section: Discussionmentioning
confidence: 99%